DEVELOPMENT OF CHATBOTS TO PROMOTE COMMUNICATION AND WORKING OF PROFESSORS AND OFFICIALS, DEPARTMENT OF EDUCATIONAL TECHNOLOGY, FACULTY OF EDUCATIONAL, KASETSART UNIVERSITY - Changsee, Jariyaporn; Diteeyont, Watsatree; Plangsorn, Boonrat (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this study were to 1) to improve a Chatbot to promote communication and working within the organization of Department of Educational Technology, Faculty of Education, Kasetsart University ‘s academic staffs 2) to investigate attitude toward Chatbot to promote communication and working within the organization of Educational Technology, Faculty of Education, Kasetsart University ‘s academic staffs by eight academic staffs Research Instrument; Chatbot KU EDTECH, attitude toward Chatbot questionnaire and attitude toward Chatbot interview form. Data was analyzed using attitude questionnaire 10 times and interviewing 2 times in 10 weeks. The finding indicates that 1) the results of chatbot quality analysis by educational technology expert from the quality assessment by 3 experts, the average was 4.65. It can be interpreted that the Chatbot is high quality. 2) the results of investigate attitude toward Chatbot, the average was 4.33. And interview of investigate attitude toward Chatbot. It can be interpreted that the user opinions agree that Chatbot can Promote Communication and Working of Professors and Officials within the organization of department of Educational Technology, Faculty of Education, Kasetsart University.